2022
DOI: 10.3390/electronics11091349
|View full text |Cite
|
Sign up to set email alerts
|

A Challenge-Based Learning Intensive Course for Competency Development in Undergraduate Engineering Students: Case Study on UAVs

Abstract: Accelerated advances in science and technology drive the need for professionals with flexible problem-solving abilities towards a collaborative working environment. The advances pose a challenge to educational institutions about how to develop learning environments that contribute to meeting the aforementioned necessity. Additionally, the fast pace of technology and innovative knowledge are encouraging universities to employ challenge-based-learning (CBL) approaches in engineering education supported by modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
1
0
2
Order By: Relevance
“…Las actuales tendencias sociales, ambientales, económicas y políticas requieren que la educación se convierta en un proceso integral dentro y fuera de las escuelas y/o universidades, brindando conocimiento en ciencias básicas, ciencias humanas y ciencias económicas transversalizados, que respondan a las necesidades multiculturales y pluriculturales globales [1], [2]. Dando como resultado, la necesidad de contar con profesionales que presenten competencias para solucionar los retos que hoy enfrentamos como humanidad.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Las actuales tendencias sociales, ambientales, económicas y políticas requieren que la educación se convierta en un proceso integral dentro y fuera de las escuelas y/o universidades, brindando conocimiento en ciencias básicas, ciencias humanas y ciencias económicas transversalizados, que respondan a las necesidades multiculturales y pluriculturales globales [1], [2]. Dando como resultado, la necesidad de contar con profesionales que presenten competencias para solucionar los retos que hoy enfrentamos como humanidad.…”
Section: Introductionunclassified
“…Además de, tener en los equipos de trabajo perfiles diferentes para lograr una multidisciplinariedad en la solución de problemas reales [8]- [10]. Esta diversidad ofrece grandes oportunidades de aprendizaje, además de lo conceptual, ya que los estudiantes trabajan en un ambiente global [1,2]. Este enfoque ha sido fuertemente acogido para la enseñanza de ciencias básicas en la mayoría de las aulas académicas se ha centrado en metodologías experimentales, por su rigurosidad metodológica y por la aceptación de los conceptos validados en la comunidad científica [3].…”
Section: Introductionunclassified
“…Additionally, other works have found that CBL improves grades contrasted to traditional learning or reduces its dispersion around the mean like explained in [41,42]. In the case of the Tec21 educational model, authors in [43][44][45] report implementations in engineering, sciences, humanities, and education finding advantages in the integration of flexible learning paths, and support for disciplinary and transversal competency development. Additionally, authors in [17,40,46] state that the CBL strategy used by Tecnologico de Monterrey results in better student grades when compared to those obtained by students enrolled in a course with a traditional teaching-learning strategy.…”
mentioning
confidence: 96%